UPPER MANTLE STRUCTURE BELOW THE DALDYN-ALAKITSK KIMBERLITE FIELD BY NUCLEAR EXPLOSION SEISMOGRAMS - Egorkin A.V. (My University, 2001)
It was established on the basis of seismograms of nuclear explosions that the upper mantle up to the depth of 410 km is characterized by chemical differentiation, which occurs as alternating layers with low and high body wave velocities. In the upper mantle-lower mantle transition zone, a seismic interface is present at 520 km. The interface geometry in the transition zone is evidence of mantle warming up to a depth of 350-660 km below the kimberlite field.